2013
DOI: 10.1371/journal.pone.0065995
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Role of BRAF Mutation in Metastatic Colorectal Cancer Receiving Anti-EGFR Monoclonal Antibodies: A Meta-Analysis

Abstract: BackgroundBRAF mutation has been investigated as a prognostic factor in metastatic colorectal cancer (mCRC) undergoing anti-EGFR monoclonal antibodies (moAbs), but current results are still inconclusive. The aim of this meta-analysis was to evaluate the relationship between BRAF mutation status and the prognosis of mCRC patients treated with moAbs.MethodsEligible studies were identified by systematically searching Pubmed, the Cochrane Library, Web of Knowledge, and OVID. Risk ratio (RR) for overall response ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
91
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 47 publications
4
91
0
4
Order By: Relevance
“…There is a link between BRAF V600E status and worse prognosis (36,37) and BRAF V600E and more advanced cancer, being mostly present in right-sided tumours (38,39). As discussed before, BRAF V600E has been found to interfere with KRAS occasionally.…”
Section: Discussionmentioning
confidence: 83%
“…There is a link between BRAF V600E status and worse prognosis (36,37) and BRAF V600E and more advanced cancer, being mostly present in right-sided tumours (38,39). As discussed before, BRAF V600E has been found to interfere with KRAS occasionally.…”
Section: Discussionmentioning
confidence: 83%
“…BRAF mutations are often associated with aggressiveness, poor differentiation and resistance to therapy in CRC (4). CRC patients with BRAF V600E mutations exhibit a poor prognosis and a poor response to panitumumab and cetuximab, monoclonal antibodies targeting the epidermal growth factor receptor (EGFR/ERBB1) (6).…”
Section: Introductionmentioning
confidence: 99%
“…BRAF activating mutations occur in about 8% of advanced disease patients with CRC 47,48 and in approximately 14% of patients with localized stage II and III CRC. 8,49 As such, mutations in BRAF constitute a substantial subset of patients with CRC.…”
mentioning
confidence: 99%
“…A recent publication of the PETACC-8 (oxaliplatin, fluorouracil, and leucovorin with or without cetuximab in patients with resected stage III colon cancer randomised phase 3) trial reported that trials in the adjuvant setting should consider mismatch repair, BRAF, and KRAS status for stratification, since BRAF p.V600 and KRAS mutations were associated with shorter DFS and OS in patients with microsatellite-stable colon cancer but not in those with tumors with MSI. 60,61 This recommendation is supported by seven systematic reviews, 20,47,48,[50][51][52][53] three of which included meta-analysis. 47,48,53 None of the systematic reviews reported the composition of their panel, so multidisciplinary panel representation could not be confirmed, and none reported patient representation on the panel.…”
mentioning
confidence: 99%
See 1 more Smart Citation